Methods for calculating the electrode position Jacobian for impedance imaging. (16th February 2017) - Boyle, A; Crabb, M G; Jehl, M; Lionheart, W R B; Adler, A
Abstract: Electrical impedance tomography (EIT) or electrical resistivity tomography (ERT) current and measure voltages at the boundary of a domain through electrodes. Significance: The movement or incorrect placement of electrodes may lead to modelling errors that result in significant reconstructed image artifacts. These errors may be accounted for by allowing for electrode position estimates in the model. Movement may be reconstructed through a first-order approximation, the electrode position Jacobian. A reconstruction that incorporates electrode position estimates and conductivity can significantly reduce image artifacts. Conversely, if electrode position is ignored it can be difficult to distinguish true conductivity changes from reconstruction artifacts which may increase the risk of a flawed interpretation. Objective: In this work, we aim to determine the fastest, most accurate approach for estimating the electrode position Jacobian. Approach: Four methods of calculating the electrode position Jacobian were evaluated on a homogeneous halfspace. Main results: Results show that Fréchet derivative and rank-one update methods are competitive in computational efficiency but achieve different solutions for certain values of contact impedance and mesh density.